Manajemen Risiko Bisnis Jasa Ekspedisi J&T Express di Suradadi Kabupaten Tegal - Armanda, Reza Rizky; Amirah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the implementation of risk management at PT J&T Express Suradadi, Tegal Regency, as one of the branches of an expedition service company with a high level of operational complexity. Daily distribution, package management, and delivery services have the potential to cause various risks, such as operational risks, service risks, risks of late delivery, risks of damaged goods, and risks of customer complaints. This study uses a qualitative descriptive approach through field observations, interviews with operational and customer service employees, and analysis of company documents. The results show that PT J&T Suradadi has implemented risk management measures that include risk identification, measuring the impact and likelihood of risks, and managing risks through standard operating procedures (SOPs), courier training, and package tracking systems. However, there are several risks that still require more attention, especially in the aspects of delay risk mitigation, increasing the accuracy of goods tracking, and responding to customer complaints. This study is expected to be the basis for improving risk management strategies to improve the service quality and operational reliability of PT J&T Express Suradadi in Tegal Regency.